SOCIALIZATION AND MAPPING OF OYSTER FINDERS' CHARACTERISTICS IN THE EFFORTS TO MANAGE THE KRUENG CUNDA WATER ENVIRONMENT, LHOKSEUMAWE CITY - Ekamaida; Dewi Kumala Sari (International Review of Practical Innovation, Technology and Green Energy (IRPITAGE), 2025)
Coastal communities in Lhokseumawe City are highly dependent on aquatic resources, one of which is through oyster harvesting. This activity has become part of the community's traditions and lifestyle, utilizing natural resources in a simple way and has been passed down from generation to generation. This community service program was conducted to identify the social characteristics of oyster gatherers and encourage sustainable oyster management in the Krueng Cunda area. The methods used included outreach and a questionnaire survey. Data were obtained through interviews and direct observation with 30 residents who were gathering oysters at several coastal locations in Lhokseumawe. Descriptive analysis was conducted to describe the general profile of oyster gatherers. The results showed that most oyster gatherers were of productive age and the majority were women. This activity is carried out with simple tools and is heavily influenced by tidal conditions. In addition to serving as a source of income, oyster gathering also has social and cultural value because it is carried out collectively and passed down within families. This condition reflects the close relationship between the community and the coastal environment. Therefore, efforts are needed to manage oysters sustainably while improving the welfare of coastal communities.